Strain gauge analysis of implant-supported, screw-retained metal frameworks: Comparison between different manufacturing technologies. (September 2016) - Degidi, Marco; Caligiana, Gianni; Francia, Daniela; Liverani, Alfredo; Olmi, Giorgio; Tornabene, Francesco
Over the past decades, the technological development in the medical field, coupled with the ongoing scientific research, has led to the development and improvement of dental prostheses supported by screw-retained metal frameworks. A key point in the manufacture of the framework is the achievement of a passive fit, intended as the capability of an implant-supported reconstruction to transmit minimum strain to implant components as well as to the surrounding bone, when subject to any load. The fitting of four different kinds of screw-retained metal frameworks was tested in this article. They differ both in materials and manufacturing process: two frameworks are made by casting, one framework is made by computer-aided design and computer-aided manufacturing and one framework is made by electric resistance spot welding (WeldONE, DENTSPLY Implants Manufacturing GmbH, Mannheim, Germany). The passivity of the frameworks was evaluated on the entire system, composed of a resin master cast, the implant analogues embedded in the cast and the frameworks. Strains were recorded by means of an electrical strain gauge connected to a control unit for strain gauge measurements. The experimental tests were carried out in the laboratories of the Department of INdustrial engineering at the University of Bologna. The results of the test campaigns, which compared three samples for each technological process, showed that no significant differences exist between the four framework types. In particular, the frameworks made by the resistance welding approach led to a mechanical response that is well comparable to that of the other tested frameworks.